Content and Context of Kaṇakkatikāram Manuscripts: Pre-Modern Malayalam Elementary Mathematics - Wagner, Roy; Ashokan, Arun (History of Science in South Asia, 2024)
Kaṇakkatikāram is the title of elementary mathematical treatises that focus on measurements, calculation techniques and practical-recreational word problems. These treatises enjoyed substantial distribution in medieval and colonial Tamil Nadu and Kerala (Parameswara Iyer 1990, Vol. 2, 524-527). In this paper we will describe these treatises based on Malayalam manuscripts. We will discuss their content, linguistic and stylistic form, context of use, relation to actual professional practices, the cultural values that they express, and the political-economic reality that they reflect. Since the Tamil versions have already been analyzed in Senthil Babu (2022), here we focus on aspects that complement his analysis and on features that are unique to, or more salient in, the Malayalam versions.